Relationship Between Peripheral Serum Adiponectin and Cerebrospinal Fluid TNF-α, IL-1β, Lactic Acid, Pyruvic Acid and Perioperative Neurocognitive Dysfunction in Elderly Patients Undergoing Hip Arthroplasty - Guo L; Wang D; Lai X; Chi Y; Liu S; Su X; Chen H; Su B; Xie H (Clinical Interventions in Aging)
Lideng Guo,1,2 Di Wang,2,3 Xiawei Lai,3,4 Yuqing Chi,3 Shuxian Liu,2,3 Xiaoqun Su,3 Huiqun Chen,3,5 Baiqin Su,3,5 Haihui Xie3,5 1Department of Anesthesiology, The Sixth Affiliated Hospital, South China University of Technology, Foshan, People’s Republic of China; 2Guangdong Medical University, Zhanjiang, People’s Republic of China; 3Department of Anesthesiology, The Tenth Affiliated Hospital of Southern Medical University, Dongguan, People’s Republic of China; 4Department of Anesthesiology, Shenzhen Traditional Chinese Medicine Hospital, Guangzhou University of Traditional Chinese Medicine, Shenzhen, People’s Republic of China; 5Dongguan Key Laboratory of Anesthesia and Organ Protection, Dongguan, People’s Republic of ChinaCorrespondence: Haihui Xie, Email xhh900@163.comBackground: Postoperative neurocognitive dysfunction (PND) represents a form of cognitive impairment related to surgery and anesthesia, which may manifest hours or even weeks after the surgical procedure, persist, and potentially progress into Alzheimer’s disease. The etiology of PND is intricate, with central nervous inflammation playing a crucial role. The clinical manifestations of PND are not distinctive, no obvious image alterations are observable, and the diagnosis rate is relatively low, thereby influencing prognosis and augmenting postoperative complications and mortality. The optimal treatment approach for PND lies in timely identification and management of the high-risk factors causing PND and implementing early prevention. We hypothesize that the level of peripheral blood adiponectin (APN) is correlated with PND, potentially through inhibiting the central inflammatory response and regulating brain energy metabolism.Methods: Fifty elderly patients undergoing elective hip arthroplasty under continuous epidural spinal anesthesia (CESA) were included. Cognitive function was assessed using the Mini-Mental State Examination (MMSE) preoperatively and postoperatively at 1, 2, 3, and 7 days. Serum APN and CSF levels of TNF-α, IL-1β, lactic acid, and pyruvic acid were measured. The occurrence of PND was recorded, and the patients were divided into a PND group and a non-PND group.Results: PND occurred in 16 patients (34.04%). The PND group had lower serum APN levels and higher cerebrospinal fluid (CSF) concentrations of TNF-α, IL-1β, and lactic acid compared to the non-PND group. CSF TNF-α and IL-1β levels were negatively correlated with serum APN concentration. These biomarkers are associated with PND occurrence and have high diagnostic value.Conclusion: Decreases in serum APN and increases in TNF-α, IL-1β, and lactic acid in CSF may be involved in the pathophysiological process of PND in elderly patients after surgery.Keywords: adiponectin, central inflammation, energy metabolism, perioperative neurocognitive dysfunction